Perselingkuhan Menjadi Penyebab Perceraian dalam Rumahtangga - Habibah Riza Azzahra; Indah Fatmawati (Institut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2026)
Infidelity can be a compelling reason for divorce due to a breach of trust in a marriage, but strong evidence is required to present it to the court. Infidelity also has emotional repercussions and can lead to more complex conflicts. Data from January to March 2025 shows that there were 800-900 divorce cases in the West Jakarta City Religious Court due to economic factors and infidelity. This is certainly interesting to study because the reasons for infidelity vary. This study aims to examine the underlying causes of infidelity in marriages and provide solutions for avoiding this heinous act. Furthermore, the research was conducted using a literature review method with a case study approach, and the analysis was descriptive. From this analysis, it can be concluded that infidelity is a strong reason for divorce, with various reasons, and the solution to avoiding infidelity is to strengthen communication and romance in the relationship.